Analysis of Family Life After The Death Of The Father In The Novel “ Saturday with Bapak” - Amelia Hafizhah Ningrum; Marudut Bernadtua Simanjuntak (International Journal of Education and Literature, 2022)
The novel “ Saturday with Bapak” by Aditya Mulya. This book tells about the life journey of a family without a father figure. The father character in this book is told to die of cancer. The back-and-forth plot of this novel makes this novel even more interesting to read. Readers seem to be able to feel the story. Adhitya Mulya’s success as a writer for a series of very touching messages about family was also followed and supported by the success of the film " Saturday Together " which was adapted from the novel. In addition, in this novel or film, it seems that there are many positive things that can be applied to the family who reads it. The study in this paper aims to analyze the life experienced by Satya and Cakra as the son of their father after the death of their father. The method used in this research is descriptive qualitative analysis. The source of research data comes from the novel and also the film " Saturday with Bapak ".